PENGARUH PENGUMUMAN LAPORAN AUDIT WAJAR TANPA PENGECUALIAN TERHADAP HARGA SAHAM PADA PERUSAHAAN JASA KEUANGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Yang Terdaftar Di BEI) - Doa Tri Arinda; M. Syafruddin (Diponegoro Journal of Accounting, 2013)
This study aims to investigating the influence annauncement unqualified audit reports on share price. And the influence audit quality on announcement unqualified opinion on share price at financing firm which list bursa efek indonesia.A even study conductd for investigating influence announcement unqualified audit reports on share price . And for investigating influence audit quality on announcement unqualified audit report on share price of financial firm list Bursa Efek Indonesai (BEI) during the period 2007,2008,2009,2010 and 2011.The conclusions of the study showed that there is no clear or significant influence of announcement unqualified audit reports on share price .And not significant also of influence audit quality on announcement unqualified audit report on shre price.